2021
DOI: 10.3390/app11199090
|View full text |Cite
|
Sign up to set email alerts
|

Design of Augmented Reality Training Content for Railway Vehicle Maintenance Focusing on the Axle-Mounted Disc Brake System

Abstract: Light maintenance training for electric multiple-unit components of the organization of railway operations is generally conducted using maintenance manuals and work videos, following the guidelines of each organization. These manuals are in the form of booklets, complicated and inconvenient for maintenance operators to carry. Therefore, training content that visualizes maintenance procedures in a three-dimensions (3D) space is necessary to overcome the drawbacks of booklet-type training. In this study, we deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The advancement of computer technology has facilitated the integration of 3D technology in skill training programs, including automobile maintenance training [37], railway axle disc brake maintenance [38], tunnel fire emergency drills [39], ship fire emergency drills [40], railway workers' skill training [41], and train crew management [42]. The use of 3D technology enables the creation of a natural world in the information space that dynamically simulates disaster occurrences with negative outcomes, such as damages, losses, injuries, and fatalities.…”
Section: Emergency Drill Based On 3d Technologymentioning
confidence: 99%
“…The advancement of computer technology has facilitated the integration of 3D technology in skill training programs, including automobile maintenance training [37], railway axle disc brake maintenance [38], tunnel fire emergency drills [39], ship fire emergency drills [40], railway workers' skill training [41], and train crew management [42]. The use of 3D technology enables the creation of a natural world in the information space that dynamically simulates disaster occurrences with negative outcomes, such as damages, losses, injuries, and fatalities.…”
Section: Emergency Drill Based On 3d Technologymentioning
confidence: 99%
“…Recently, most of the AR application cases for maintenance in the railway vehicle sector have been developed mainly on main mechanical equipment such as boogie and braking devices conducted by the research group of the National University of Transportation in Korea [23,24]. In the case of the air compressor conducted in this study, only some applications have been reported to manufacture industrial screw-type air compressors [25].…”
Section: Introductionmentioning
confidence: 96%
“…Accordingly, the importance of systematic maintenance education is emerging. Therefore, to enhance the training effect of maintenance staff as well as overcome the shortcomings of booklet-type manuals, developing 3D learning content using AR technique is essential [3].…”
Section: Introductionmentioning
confidence: 99%